Hyperkalemia: A persisting risk. A case report and update on current management. Issue 9 (2nd June 2020) - Schnaubelt, Sebastian; Niederdoeckl, Jan; Schoergenhofer, Christian; Cacioppo, Filippo; Schuetz, Nikola; Spiel, Alexander O.; Hecking, Manfred; Domanovits, Hans
Abstract: We report a case of hemodynamic instability due to bradycardia on the basis of severe hyperkalemia. Diabetic ketoacidosis and acute kidney injury together with polypharmacy triggered the acute onset. Potentially life‐threatening hyperkalemia is often induced by drug interactions. ECG features may be crucial for diagnosis, and treatment depends on setting and resources. Abstract : We report a case of hemodynamic instability due to bradycardia on the basis of severe hyperkalemia. Diabetic ketoacidosis and acute kidney injury together with polypharmacy triggered the acute onset. Potentially life‐threatening hyperkalemia is often induced by drug interactions. ECG features may be crucial for diagnosis, and treatment depends on setting and resources.